2016
DOI: 10.1111/php.12654
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Properties of Amine‐substituted Analogues of Firefly Luciferin and Oxyluciferin

Abstract: Spectroscopic and photophysical properties of firefly luciferin and oxyluciferin analogues with an amine substituent (NH , NHMe and NMe ) at the C6' position were studied based on absorption and fluorescence measurements. Their π-electronic properties were investigated by DFT and TD-DFT calculations. These compounds showed fluorescence solvatochromism with good quantum yields. An increase in the electron-donating strength of the substituent led to the bathochromic shift of the fluorescence maximum. The fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“… 39 , showed that L. cruciata luciferase displays a close active site conformation with the critical luciferyl-adenylate intermediate analog, DLSA, and an open one with the products AMP and oxyluciferin. Later studies with 6′-aminoluciferin analogs supported the existence of two binding modes for oxyluciferin in firefly luciferases active site, an apolar (N) responsible for green light emission and another polar (P) responsible for red emission 21 , 22 . The active site in firefly luciferases may undergo conformational changes between these two extremes, and the light emitting step may take place somewhere between these two conformations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 39 , showed that L. cruciata luciferase displays a close active site conformation with the critical luciferyl-adenylate intermediate analog, DLSA, and an open one with the products AMP and oxyluciferin. Later studies with 6′-aminoluciferin analogs supported the existence of two binding modes for oxyluciferin in firefly luciferases active site, an apolar (N) responsible for green light emission and another polar (P) responsible for red emission 21 , 22 . The active site in firefly luciferases may undergo conformational changes between these two extremes, and the light emitting step may take place somewhere between these two conformations.…”
Section: Discussionmentioning
confidence: 97%
“…Among the specific interactions, the presence of bases near the thiazinic side of the luciferin binding site assisting the tautomerization between a keto and enol forms has been originally claimed to explain green to red bioluminescence color change in firefly luciferases 9 , 13 . More recently, interactions influencing the resonance forms of excited oxyluciferin 20 , specific acid-base and finally electrostatic effects around oxyluciferin 6′ phenol group are being considered to determine bioluminescence colors 18 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…We therefore used the alternative 1b conformation in the remainder of the analyses. Kakiuchi and Hirano reported a similar near‐degeneracy for the two conformations in the ground state, but found a smaller difference of 5 nm when the S 0 ➔ S 1 absorption was considered . In Figure we show the experimentally measured emission wavelengths against the predicted wavelengths with the best performing level of theory, with the outlier indicated.…”
Section: Resultsmentioning
confidence: 78%
“…Chen and Lindh examined the effect of the medium on the spectra . More recently, a larger number of luciferin/oxyluciferin analogues have been studied, but comparison with experimentally measured emission wavelengths has been relatively limited …”
Section: Introductionmentioning
confidence: 99%
“…The extraction of the contribution due to each oxyluciferin form to the absorption or emission spectra is often tedious . For that reason, oxyluciferin analogues have been proposed and synthesized for inhibiting certain forms . In this work, we are interested in a particular set of analogues (Figure , right), studied both experimentally and theoretically .…”
Section: Introductionmentioning
confidence: 99%